2014
DOI: 10.1007/s00300-014-1542-6
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton community composition and photosynthetic physiology in the Australian sector of the Southern Ocean during the austral summer of 2010/2011

Abstract: Phytoplankton population dynamics play an important role in biogeochemical cycles in the Southern Ocean during austral summer. However, the relationship between phytoplankton community composition and primary productivity remains elusive in this region. We investigated the community composition and photosynthetic physiology of surface phytoplankton assemblages in the Australian sector of the Southern Ocean from December 2010 to January 2011. There were significant latitudinal variations in hydrographic and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…1c and d). This pattern is broadly confirmed by observations: the latitudinal range of elevated coccolithophore biomass in the model agrees well with the observed location of the GCB (Balch et al, 2011), an area of elevated PIC levels between 40 and 60 • S that has frequently been linked to high coccolithophore abundance (Trull et al, 2018;Balch et al, 2016;Saavedra-Pellitero et al, 2014;Poulton et al, 2013;Hinz et al, 2012). Maximum coccolithophore abundances in the upper 50 m of the water column of up to ≈ 2500 cells mL −1 (2.7 mmol C m −3 , biomass conversion following O'Brien et al, 2013) have been reported for the Patagonian Shelf ( Fig.…”
Section: Phytoplankton Biogeography and Community Composition In The Sosupporting
confidence: 87%
See 3 more Smart Citations
“…1c and d). This pattern is broadly confirmed by observations: the latitudinal range of elevated coccolithophore biomass in the model agrees well with the observed location of the GCB (Balch et al, 2011), an area of elevated PIC levels between 40 and 60 • S that has frequently been linked to high coccolithophore abundance (Trull et al, 2018;Balch et al, 2016;Saavedra-Pellitero et al, 2014;Poulton et al, 2013;Hinz et al, 2012). Maximum coccolithophore abundances in the upper 50 m of the water column of up to ≈ 2500 cells mL −1 (2.7 mmol C m −3 , biomass conversion following O'Brien et al, 2013) have been reported for the Patagonian Shelf ( Fig.…”
Section: Phytoplankton Biogeography and Community Composition In The Sosupporting
confidence: 87%
“…Ultimately, coccolithophore growth and calcification in BEC are currently not dependent on ambient CO 2 concentrations. However, both the study by Trull et al (2018) and the review by Krumhardt et al (2017) suggest carbonate chemistry to be of minor importance in controlling the relative importance of coccolithophores in the SO at present, as both specific growth rates and CaCO 3 : C org production ratios of SO coccolithophores appear rather insensitive to variations in ambient CO 2 (Krumhardt et al, 2017). Concurrently, the CaCO 3 : C org production ratio has been shown to depend on surrounding temperature, light, and nutrient levels.…”
Section: Limitations and Caveatsmentioning
confidence: 99%
See 2 more Smart Citations
“…2a & Fig. 3 Takao et al, 2014). In ROMS-BEC, the summer phytoplankton community south of 60 • S is often almost solely composed of diatoms ( Fig.…”
mentioning
confidence: 98%